DETERMINAN PEMBIAYAAN MURABAHAH BANK UMUM SYARIAH DI INDONESIA - Tony S. Chendrawan (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2017)
This research aims to analyze the effect of external factors: M1, inflation, SWBI and internal factors: NPF to Murabaha financing on Islamic banking. The data used are the time series data for the period of June 2010-June 2015, published by Bank Indonesia and OJK (Financial Services Authority) of the Sharia Banking statistics report. Methods of analysis used in this research are using Multiple Linear Regression method is Ordinary Least Square (OLS). The results of this research indicate that the variable is positive and significant effect of inflation towards financing the murabaha. Variable M1 and inflation influence positively and significantly to the financing of Murabaha. While the SWBI variable does not affect the financing of Murabaha. And internal factors namely NPF has a negative influence and significantly to the financing of Murabaha